44 CONTENT VALIDITY OF THE DYSPHAGIA PREVALENCE AND PRACTICES IN RESIDENTIAL LONG-TERM CARE SETTINGS SURVEY. (25th October 2022) - Artiles, CE; Regan, J; Donnellan, C
Abstract: Background: Dysphagia is common in older adults living in Residential Long-Term Care (RLTC) settings, requiring timely diagnosis and appropriate management to avoid potential complications and improve quality of life. Current dysphagia prevalence rates, screening and management practices in RLTC settings in the Republic of Ireland are not known. Methods: An online survey was developed, consisting of 40 questions to determine dysphagia prevalence rates and associated nursing practices in screening and managing dysphagia in RLTC settings. An expert panel was formed with individuals having clinical experience in swallow screening and dysphagia management in older adults. We calculated Item-level Content Validity Index (I-CVI) and modified Kappa statistic (k), to adjust for chance agreement, for all 40 items in terms of representativeness and clarity. A survey item is considered relevant where I-CVI≥0.78, between 0.70 and 0.77 requires revision, and below 0.70, is eliminated. For k values, agreement levels are considered as low (k=< 0.40), fair (k=0.40–0.59), good (k=0.60–0.74) and high (k=≥ 0.75). Results: The expert panel consisted of three nurse managers, two nurse specialists and three senior speech and language therapists with postgraduate qualifications, up to three years of experience in dysphagia related research and three to thirty-six years of clinical practice. For clarity, all items scored I-CVI≥0.78 and k=≥0.75 except four items, for which I-CVI=0.75 and k=0.72. For representativeness, only one item had an I-CVI=0.75 and k=0.72, with all other scoring I-CVI≥0.78 and k=≥ 0.75. Conclusion: Findings suggest that the DPP-RLTCS has high content validity in terms of clarity and representativeness even after adjusting for chance agreement.